Boiling Point - Barantini, Philip; Lewis, Matthew; Graham, Stephen; Robinson, Vinette; Feetham, Alice (Second Sight, 2022)
On the busiest night of the year at one of the hottest restaurants in London, a charismatic and commanding head chef balances on a knife's edge as multiple personal and professional crises threaten to destroy everything he's worked for. [secondsightfilms.co.uk]